Mutation Update for GNE Gene Variants Associated with GNE Myopathy. Issue 8 (August 2014) - Celeste, Frank V.; Vilboux, Thierry; Ciccone, Carla; de Dios, John Karl; Malicdan, May Christine V.; Leoyklang, Petcharat; McKew, John C.; Gahl, William A.; Carrillo‐Carrasco, Nuria; Huizing, Marjan
<x xml:space="preserve">Abstract</x> This is a comprehensive report of GNE gene mutations associated with GNE myopathy. All Reported human GNE variants are scattered all throughout the coding regions of the gene. Based on allele frequencies, the worldwide prevalence of GNE myopathy is estimated to be higher (∼4‐21/1, 000, 000) than previously thought <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>